Linguistic Distance : A Quantitative Measure of the Distance Between English and Other Languages - Paul W. Miller; Barry R. Chiswick (Institute for the Study of Labor (IZA), 2004)
This paper develops a scalar or quantitative measure of the ?distance? between English and a myriad of other (non-native American) languages. This measure is based on the difficulty Americans have learning other languages. The linguistic distance measure is then used in an analysis of the determinants of English language proficiency among adult immigrants in the United States and Canada. It is shown that, when other determinants of English language proficiency are the same, the greater the measure of linguistic distance, the poorer is the respondent?s English language proficiency. This measure can be used in research, evaluation and practitioner analyses, and for diagnostic purposes regarding linguistic minorities in English-speaking countries. The methodology can also be applied to develop linguistic distance measures for other languages.
Keywords: J24; J15; I29; 330; immigrants; language proficiency; linguistic distance; Migranten; Fremdsprache; Englisch; Mehrsprachigkeit; Vereinigte Staaten